Cytotoxin-Associated Gene A-Negative Helicobacter pylori Promotes Gastric Mucosal CX3CR1+CD4+ Effector Memory T Cell Recruitment in Mice - Sun, Heqiang; He, Taojun; Wu, Yanan; Yuan, Hanmei; Ning, Jie; Zhang, Zhenhua; Deng, Xinli; Li, Bin; Wu, Chao (Frontiers in Microbiology, 2022)
Background Helicobacter pylori can cause many kinds of gastric disorders, ranging from gastritis to gastric cancer. Cytotoxin-associated gene A (CagA)+H. pylori is more likely to cause gastric histopathologic damage than CagA–H. pylori. However, the underlying mechanism needs to be further investigated. Materials and methods Mice were intragastrically administered equal amounts of CagA+ or CagA–H. pylori. Four weeks later, 24 chemokines in stomachs were measured using a mouse chemokine array, and the phenotypes of the recruited gastric CD4+ T cells were analyzed. The migration pathway was evaluated. Finally, the correlation between each pair among the recruited CD4+ T cell sub-population, H. pylori colonization level, and histopathologic damage score were determined by Pearson correlation analysis. Results The concentration of chemokines, CCL3 and CX3CL1, were significantly elevated in CagA–H. pylori-infected gastric mucosa than in CagA+H. pylori-infected gastric mucosa. Among them, CX3CL1 secreted by gastric epithelial cells, which was elicited more effectively by CagA–H. pylori than by the CagA+ strain, dramatically promoted mucosal CD4+ T cell migration. The expression of CX3CR1, the only known receptor of CX3CL1, was upregulated on the surface of gastric CD4+ T cells in CagA–H. pylori-infected stomach. In addition, most of the CX3CR1-positive gastric CD4+ T cells were CD44+CD69–CCR7– effector memory T cells (Tem). Pearson correlation analysis showed that the recruited CX3CR1+CD4+ Tem cell population was negatively correlated with H. pylori colonization level and histopathologic damage score. Conclusion CagA–H. pylori promotes gastric mucosal CX3CR1+CD4+ Tem recruitment in mice.